ANALISIS MANFAAT KOPERASI DAN TINGKAT PARTISIPASI ANGGOTA KOPERASI SIMPAN PINJAM (KSP) SUBUR MAKMUR SEJAHTERA KECAMATAN SEPUTIH BANYAK KABUPATEN LAMPUNG TENGAH - Dwi Febrina; Dyah Aring Hepiana Lestari; Indah Nurmayasari (Lampung University, 2019)
This research aims to analyze the economic and noneconomic benefits received by the members, the participation level of cooperative members and affecting factors. This research was purposively conducted at KSP Subur Makmur Sejahtera, Seputih Banyak, Central Lampung Regency from January to February 2018 with 48 respondents randomly taken by using Simple Random Sampling method. Data were collected by using a survey method and were analyzed descriptively using Customer Satisfaction Index (CSI) and Seemingly Unrelated Regressions (SUR). The results showed that the average of economic benefits received was Rp789,05.,62 per year, and noneconomic benefits received as the satisfaction level of cooperative members was classified at the level of satisfied members. The participation level of the cooperative members attending annual meeting, paying compulsory savings, and utilizing the cooperative enterprises were each considered as average, low, and high category. Factors which affected members to participate in attending annual meeting were age, formal and nonformal education, the number of dependent family members, noneconomic benefits, distance, and members’ perception. Mean while formal education, noneconomic benefits, and distance affected the participation level of compulsory savings payment. Lastly, ages, formal and nonformal education, the number of dependent family members, economic benefits, and distance affected the utilization of cooperative enterprises.Key words : cooperative, members, benefits, participation